Zinc ion as effective film morphology controller in perovskite solar cells. Issue 5 (3rd April 2018) - Chen, Renjie; Hou, Dagang; Lu, Chaojie; Zhang, Jing; Liu, Peng; Tian, Hui; Zeng, Zhaobing; Xiong, Qi; Hu, Ziyang; Zhu, Yuejin; Han, Liyuan
Abstract : There exists stronger chemical interaction between Zn 2+ and CH3 NH3 + /I −, which effectively influences the morphology of perovskite film during annealing process. Abstract : Over the past several years, organic–inorganic hybrid perovskite solar cells have developed rapidly. One of the hot topics with perovskite solar cells is how to achieve a high quality perovskite thin film. A Lewis acid–base adduct is effective for controlling perovskite morphology during the film preparation process. Zinc ion (Zn 2+ ) is a stronger Lewis acid than lead ion (Pb 2+ ) and it has a high ability to coordinate with methylamine groups (CH3 NH3 + ), so it is doped into perovskite precursors to substitute for Pb 2+ to influence crystallization during the annealing process. In this work, by adjusting zinc ion's concentration, high quality perovskite films with larger grain sizes and fewer pinholes were obtained. Finally, the average power conversion efficiency (PCE) of solar cells based on optimal concentration reached to 16.3% (with an open circuit voltage of 1.06 V, short circuit current density of 21.98 mA cm −2, and fill factor of 70%), resulting in a 34.7% improvement compared to a pristine one. Our work highlights the metal-ion additive as an effective method to control perovskite film quality.